Associação do ômega-3 e ácido úrico sérico com a qualidade muscular em adultos: NHANES 2011-2012 - Barbosa, Cinthia Domingos (2022)
Introduction: Muscle quality (QM) is defined as the muscle's ability to produce force per unit of muscle mass. It is an important measure as it is associated with quality of life. Therefore, it becomes important to know what some possible factors are associated with QM. Both omega-3 and uric acid (AU) have been studied for their possible benefits in muscle health due to their anti-inflammatory or antioxidant properties, respectively. Objective: To associate plasma omega-3 and AU levels with BM in adults (20 to 59 years) participating in the National Health and Nutrition Examination Survey (NHANES). Methodology: A cross-sectional study was carried out, which included men and women aged between 20 and 59 years, from NHANES, with data obtained from the 2011-2012 cycles. Handgrip strength was evaluated using a dynamometer and body composition was accessed using dual energy bone absorptiometry (DEXA). The BQ ratios were calculated by dividing the sum of arm strength values by the lean arm mass (BQ); and the values of the sum of the strength of the arms by the lean appendicular mass (AQ). Linear regression analysis was performed without (Model 1) and with adjustments (Model 2). Results: Regarding omega-3, in the analysis without adjustment for confounding factors, there was an association only between the values of omega-3 alpha linolenic (ALA) and the QMB ratio (β = -0.004 p = 0.006). However, after adjusting for confounders, this association was not significant. Regarding QMA, there was no association with omega-3 in both models. Regarding AU, in the analysis without adjustment for confounding factors, there was an association between AU and the total sample (β = -0.571, p = <0.001) and for women (β = -0.651, p = <0.001) with the QMB ratio. In the adjusted analysis, the association remained in the total sample (β = -0.124 p = <0.021) and for women (β = - 0.197 p = 0.001). Regarding the AQ ratio, there was an association of AU for men (β = - 0.060 p = 0.002) and women (β = -0.130 p = <0.001) only in the model without adjustment for confounding factors. Conclusion: Plasmatic omega-3 levels were not associated with MQ ratios in adult men and women and plasmatic AU levels were negatively associated with QMB only in women.